2020
DOI: 10.36483/vanvetj.540404
|View full text |Cite
|
Sign up to set email alerts
|

Macroanatomical and Morphometric Investigation of Mandibula in Aksaray Malaklı Dogs

Abstract: In this investigation, mandible of 5 adult Aksaray Malaklı dogs, regardless of gender, aged between 4 and 5 years, who died from various reasons, brought to Aksaray University Veterinary Faculty Veterinary Health and Application and Research Center by Aksaray Malaklı dog breeders between 2016-2018, were used. After determining the macroanatomical features of the study, morphometric investigations were measured with the help of digital caliper and the data were analyzed with arithmetic mean and standard error. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A previous study found that the fossa masseterica of carnivores is deep and the processus coronoideus is wide (Karan et al, 2005). In wolf and fox, processus coronoideus goes upright; the lynx, cat and dog were said to be headed backwards (İlgün & Özüdoğru, 2020). However, in this study, the shape differences between cats and dogs were also statistically revealed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study found that the fossa masseterica of carnivores is deep and the processus coronoideus is wide (Karan et al, 2005). In wolf and fox, processus coronoideus goes upright; the lynx, cat and dog were said to be headed backwards (İlgün & Özüdoğru, 2020). However, in this study, the shape differences between cats and dogs were also statistically revealed.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological studies showing that these structures are different in carnivores are available in the literature (Evans, 1979). Processus coronoideus is directed upwards in wolf and fox; and backwards in the lynx, cat and dog (İlgün & Özüdoğru, 2020; Karan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…ksaray Malakli dog is the most recognized dog breed among the Karabaş and the Sivas Kangal breeds. It is frequently bred in Aksaray, Nevşehir, and Şereflikoçhisar regions of Central Anatolia (Atasoy et al, 2014;İlgün et al, 2022;İlgün & Özüdoğru, 2020). Structurally, it is distinguished from Sivas Kangal dogs by its larger body size, shorter coat, and straighter tail.…”
Section: Introductionmentioning
confidence: 99%